Sejarah Panjang Pendidikan Karakter di Indonesia Pada Era Proklamasi Kemerdekaan Sampai Era Reformasi - Abdul Miud Aris Shofa (Sekolah Tingi Keguruan dan Ilmu Pendidikan (STKIP) PGRI Tulungagung, 2020)
The purpose of writing this article is to know the development of character education in the era of the proclamation of independence, the new order, to reform and to find out the similarities and differences in the characteristics of the development of character education in Indonesia. The method used in this article is library research, which is a research method that is obtained based on literature or literature by analyzing facts and data from literature sources and documents, so as to produce an in-depth analysis. In simple steps the work of writing history used, including heuristics, criticism, interpretation, and historiography.The results of the study show that in the era of the proclamation of independence, character education aims to develop wise human beings who are wise, democratic, responsible for the welfare of society, love for the motherland, and have a high patriot spirit. Character education in the New Order era aims to form Pancasilaans as qualified, independent development individuals who can counteract teachings or understandings that are contrary to the values of Pancasila. In the reform era, the goal of character education is to form a character or character to develop a nation's civilization with dignity and noble attitudes, behaviors and actions.The equality of character education in Indonesia from the proclamation of independence to reform is the Pancasila and the 1945 Constitution used as a basis for the attitudes, behaviors, and actions of citizens. In government affairs both are used as a basis for making and making policy in the implementation of character education. Differences in character education from the proclamation of independence to reform are influenced by social, political, economic, and cultural aspects of the character education policy taken.